Density functional study of adsorption properties of NO and NH3 over CuO/γ-Al2O3 catalyst - Cao, F.; Su, Sheng; Xiang, J.; Sun, L.; Hu, S.; Zhao, Q.; Wang, P.; Lei, S. (Elsevier BV North-Holland, 2012)
Currently, selective catalytic reduction (SCR) of NOx with NH3 has been widely applied to reduce the emission of nitrogen oxides from mobile and stationary sources. But the detailed SCR reaction mechanism is still controversial and lacks the related comparative study of molecule modeling. The SCR reaction belongs to the gas–solid multiphase reaction, in which the adsorption of NH3 and NO by the catalysts plays an important role. In the present study, the adsorption properties of NH3 and NO on both the dry and partially hydroxylated γ-Al2O3 (1 1 0) surfaces supported CuO were revealed using the density-function theory (DFT) calculations. The results showed that NH3 could be adsorbed strongly on the dry (1 1 0) surface in the form of coordinated NH3 and NH4+. Some of the coordinated NH3 could then undergo H-abstraction and form the –NH2 species. NO could be adsorbed weakly on the dry surface, and could also be adsorbed as bidentate nitrates or bridged nitrites. However, the adsorption activation of NH3 and NO on the partially hydroxylated surface was much weaker. The results of the DFT calculations are in good agreement with the experimental results and provided detailed clues to understand the adsorption mechanism of NH3 and NO on the CuO/γ-Al2O3 catalysts.